Efficiency and Safety of Desferioxamine Chelation Therapy in Paediatric Patients with Transfusion-Dependent Anaemia: Experience of two Centres from Sudan - Saad, Atif Ahmed; Masaod, Samah Ahmed; Elhassan, Osman Bashir; Zulfu, Azza Ahmed (AL-Kindy College Medical Journal, 2022)
Background: Repeated blood transfusion   is   the main   therapeutic option for transfusion-dependent anaemias with consequent iron overload and organ damage .Therefore iron chelating agents are important protective measures for these patients. The aim of this study was  to investigate  the efficiency and safety of Desferroxamine  in paediatrics population subjected  to iron overload as a consequence  of repeated transfusion in a group of  Sudanese children  Subjects & Methods: This was a descriptive cross-sectional hospital based study.  Conducted in two main paediatric reference hospitals   in, Sudan. Within   the period between November 2017   and   April 2018 (6 months duration).  The   two centres were JaafarI bn- Oaf hospital and Albulk hospital.  The study population included all patients of transfusion dependent anaemia who received desferrioxamine within the study period. Hundred   patients were enrolled in the study. The study variables  were  demographic data, number of blood transfusions , serum ferritin  pre and post  blood transfusion and treatment of desferrioxaminResults: Sixty percent (60%)  of the studied cases  were males and 40% were females ,46%  were thalassemic, 46%  were sicklers,  5% aplastic anemia and 3% with red cell aplasia .The mean  serum ferritin level before starting desferoxamine  was 2.14 and after dessferoxamine  was  2.48,   P –value  was  highly significant.  The most common side effect encountered   was skin rash (36%)Conclusion: This study revealed some features of   safety and efficiency of desferoxamine therapy   in Sudanese paediatrics population affected by transfusion-dependent anemia. More studies are needed to   describe this important health problem